Feedback of Non-Local dxy Nematicity on the Magnetic Anisotropy in FeSe - Bötzel, Steffen; Eremin, Ilya M. (Frontiers in Physics, 2022)
We analyze theoretically the magnetic anisotropy in the nematic phase of FeSe by computing the spin and the orbital susceptibilities from the microscopic multiorbital model. In particular, we take into account both the xz/yz and the recently proposed non-local xy nematic ordering and show that the latter one could play a crucial role in reproducing the experimentally-measured temperature dependence of the magnetic anisotropy. This provides a direct fingerprint of the different nematic scenarios on the magnetic properties of FeSe.